2023
DOI: 10.1038/s41422-023-00788-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-localized cGAS suppresses ferroptosis to promote cancer progression

Abstract: A well-established role of cyclic GMP-AMP synthase (cGAS) is the recognition of cytosolic DNA, which is linked to the activation of host defense programs against pathogens via stimulator of interferon genes (STING)-dependent innate immune response. Recent advance has also revealed that cGAS may be involved in several noninfectious contexts by localizing to subcellular compartments other than the cytosol. However, the subcellular localization and function of cGAS in different biological conditions is unclear; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…The pivotal link between mitochondria and the innate immune was initially brought to light with the discovery of MAVS, an integral protein localized within mitochondria that plays a crucial role as an adaptor in RIG-I-like receptors signaling (Seth et al, 2005). More recently, other innate immune molecules, such as cGAS, NLRX1, TRAF6, NLRP3, and IRGM, have been functionally associated with mitochondria (Arnoult et al, 2011; Qiu et al, 2023). The accumulating evidences suggest that viruses eliminate critical immune molecules within mitochondria by reducing mitochondrial mass to evade immune response (Mehrzadi et al, 2021; Wang et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal link between mitochondria and the innate immune was initially brought to light with the discovery of MAVS, an integral protein localized within mitochondria that plays a crucial role as an adaptor in RIG-I-like receptors signaling (Seth et al, 2005). More recently, other innate immune molecules, such as cGAS, NLRX1, TRAF6, NLRP3, and IRGM, have been functionally associated with mitochondria (Arnoult et al, 2011; Qiu et al, 2023). The accumulating evidences suggest that viruses eliminate critical immune molecules within mitochondria by reducing mitochondrial mass to evade immune response (Mehrzadi et al, 2021; Wang et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mitochondrial damage can fine-tune the availability of inflammatory molecules. The stimulator of interferon genes (STING), also known as TMEM173, serves as a PRR responsible for detecting mtDNA [ 36 39 ]. ATO can serve as an immunostimulant by inducing mitochondrial damage and the release of mtDNA, thereby activating the cGAS/STING/IFN cascade.…”
Section: Discussionmentioning
confidence: 99%
“…[45] Activation and Regulation of the cGAS-STING Signaling Pathway Initial models assumed that co-localization of cGAS and DNA in the cytosol de nes the speci city of the pathway for recognizing non-self DNA. However, recent research has demonstrated that cGAS is also found in all cellular compartments (membrane, cytosol, and nucleus), [46][47][48] and this subcellular compartmentalization has been associated with the signaling speci city of cGAS. [49] The precise mechanism by which cGAS dissociates from subcellular structures and senses ds-DNA, including mtDNA, is not yet clear.…”
Section: Overview Of the Cgas-sting Signaling Pathwaymentioning
confidence: 99%